Association between probiotic therapy and the risk of hepatocellular carcinoma in patients with hepatitis B-related cirrhosis - Shi, Ke; Zhang, Qun; Zhang, Yi; Bi, Yufei; Zeng, Xuanwei; Wang, Xianbo (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: Probiotics may offer cancer-prevention benefits, based on experimental investigation results. This study aimed to determine the potential association between probiotics and hepatocellular carcinoma (HCC) in patients with hepatitis B-related cirrhosis (HBC) receiving antiviral therapy. Design: This retrospective study included 1267 patients with HBC treated with entecavir or tenofovir between January 2013 and December 2017. The risk of developing HCC was compared between two cohorts of 449 probiotic users (taking a cumulative defined daily doses [cDDD] of ≥ 28) and 818 non-probiotic users (< 28 cDDD). To eliminate the bias caused by confounding factors, propensity score matching (PSM) was used. Results: On multivariate regression analysis, probiotic consumption was an independent protective factor for HCC occurrence. After PSM, the incidence of HCC was significantly lower in the probiotic users than that in the nonusers (adjusted hazard ratio [aHR]: 0.70, 95% confidence interval: 0.59–0.83, P < 0.001). The aHRs for probiotics with 28–89, 90–180, and >180 cDDD were 0.58, 0.28, and 0.12, respectively, indicating a dose-response pattern. In 28–89, 90–180, and >180 cDDD, the 3-year cumulative incidence of HCC was 8.7%, 4.7%, and 3.0%, respectively. A multivariate stratified analysis confirmed that the administration of probiotics could help patients. Conclusion: Adjuvant probiotic therapy may reduce the risk of HCC in patients receiving antiviral medication for HBC. However, further clinical research is required to confirm these findings.